Cognitive behavioral therapy and traditional cooperative games in improving social skills: A single-subject experimental study - Dinda Permatasari Harahap (Institut Agama Islam Negeri Langsa, 2023)
This study aimed to ascertain how cognitive behavior therapy and traditional games in children could improve their social skills. This research was a single-subject experimental study. The participant was a 6-year-old kindergarten student going by the alias “Kila”. The data was collected using interview and observation methods. The CBT techniques are puppets, storytelling, visualization, and imagery techniques. Traditional games are used after the CBT sections. These games involved peer groups to increase the social skills of the participants. The traditional games used are the ones that Indonesian people used to do, such as “Cublak-cublak Suweng,” “Clogs,” “Cardboard Bridge,” “Jump Rope,” and “Word Game.”. Data were collected through observation and interviews with participants, family members, teachers, and colleagues. Information about the participant can also be obtained using psychological tools such as intellectual and socialization. Data is analyzed based on the characteristics of previous and subsequent social capacity changes. The result showed that the CBT technique for children could change the participant’s negative automatic thoughts about her friends. Those traditional games could also improve Kila’s social skills, especially in her interpersonal behavior, such as making friends, communicating, giving feedback to her peers, and being involved in some interactions and communications. CBT techniques and traditional games have an impact on increasing the social abilities of participants. This can be seen from the improvement in participants’ social skills, such as interpersonal behavior, self-behavior, academic behavior, peer acceptance, and communication skills.